Residua, Sequelae and Complications of Cardiac Defects in Adult Congenital Heart Disease after Repair at an Early Age - Sultan, Mohammad Ashraf Uddin; Sheikh, Naveen (University Heart Journal, 2025)
A cardiac malformation, also known as a congenital heart defect, is a structural problem with the heart or blood vessels that is present at birth. These abnormalities occur when the heart or blood vessels don’t form correctly in the womb. They are formed during the intra-uterine life and become visible between the 3rd and 8th week of pregnancy, when the heart is formed. Cardiac malformations include: Ventricular Septal defects, Transposition of the great vessels and Coarctation of the aorta. In most cases, the cause of cardiac malformations in unknown. Some know causes include: Maternal diabetes, Teratogens. It has been estimated that 45% of adults with congenital heart defects do not need routine follow-up in a specialized unit. For another 30%, the responsibility for care must be shared between the specialized unit and clinical cardiologist. University Heart Journal 2024; 20(1): 31-35